INNOVATIVE PEDAGOGICAL APPROACHES TO ENHANCING GOAL-SETTING COMPETENCE OF STUDENTS IN THE GLOBAL AGE - Karimova Saida O‘ktamovna (Journals Park Publishing, 2025)
This article examines innovative pedagogical approaches to enhancing students’ goal-setting competence in the global age. It highlights the growing importance of equipping learners not only with knowledge but also with the ability to set meaningful life goals, make conscious decisions, and align personal aspirations with societal needs. The study explores how modern educational practices such as student-centered learning, project-based methods, and digital literacy contribute to strengthening intrinsic motivation, developing reflective skills, and fostering responsibility among students. Particular attention is given to integrating national values with universal principles, thus preparing young learners to become active, responsible, and creative participants in a rapidly changing global society.
Keywords: Goal-setting competence, students, innovative pedagogy, global age, motivation, reflective skills, student-centered learning, national and universal values, lifelong learning.